November 2013 Phoenix pulmonary journal club: pleural catheter infection - Mathew M (Southwest Journal of Pulmonary and Critical Care, 2013)
No abstract available. Article truncated at 150 words. Tunneled indwelling pleural catheters (TPC) have revolutionized the treatment of recurrent malignant pleural effusions. Malignant pleural effusions are seen in up to 15% of advanced malignancies such as lung and breast cancer. Prior to the approval of TPC, treatment options were limited to mechanical or chemical pleurodesis. The FDA approved the use of TPC for the treatment of malignant pleural effusions (MPE) in 1997. The study published by Putnam, Light et al. (1) validated the use of tunneled pleural catheters in the management of malignant pleural effusions. Over the last decade the use of TPC has escalated. This retrospective study looks at the number of reported cases of tunneled pleural catheter related infections. The study was a retrospective chart review of done through 11 centers from the years 2001-2012. A total of 1021 patients and catheters were placed during this time frame for the management of MPE. Catheter related infections …